Penguatan Jiwa Entrepreneur Pada Usia Dini Dengan Prinsip Urban Farming Untuk Menanam Palawija Di Desa Batang Pane I - Trans Ningsih; Mesran (ORAHUA : Jurnal Pengabdian Kepada Masyarakat, 2024)
The introduction of the concept of entrepreneurship from an early age is currently not something new. By being introduced to entrepreneurship from an early age, it is hoped that children will start to get used to understanding the scope of business, get used to thinking critically and analytically. Apart from that, children also become more active and productive because they are used to doing creative things. One simple entrepreneurial activity that can be introduced to children is planting plants around the house. Some alternative plants that can be planted are secondary crops. With urban farming principles, plant planting activities carried out by children become more efficient and effective. This is because the child does not need to bother cultivating a large area of ​​land, besides that it also does not require large costs compared to clearing land for farming.